Cement-free high-chromium castable and preparation method thereof
By using cementless high chromium castables, using raw materials such as chromium oxide fuses or chromium aluminum solid solution, the use of CaO is reduced, and the problem of insufficient thermal shock performance of existing high chromium castables is solved, and better high-temperature usage performance is achieved. Slag corrosion resistance.
Patent Information
- Application Number
- CN202411697340.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
When existing high-chromium castables are used in high-temperature industries, the thermal shock performance is insufficient, resulting in the material being prone to cracks and peeling under the action of thermal stress, affecting its service life.
The cementless high chromium castable is used, and chromium oxide fuses or chromium aluminum solid solution, aluminum oxide fine powder, etc. are used as the main raw materials to prepare through vibration molding to reduce CaO in traditional aluminate cement and improve the thermal shock performance of the material.
Cementless high chromium castables exhibit better thermal shock and slag corrosion resistance at high temperatures, extending the service life of the material and reducing the risk of material damage.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory castables, and mainly relates to a cement-free high-chromium castable and a preparation method thereof. Background Art
[0002] At present, calcium aluminate water is used as the main binder in monolithic refractory castables, that is, cement-bonded castables occupy a dominant position in refractory castables. However, as the use conditions of the high-temperature metallurgical industry become more and more stringent, new requirements are also put forward for refractory materials. Thermal shock resistance is the ability of refractory materials to maintain a certain strength without failure under the action of thermal stress. Thermal stress causes cracks in refractory products, and gradually leads to crack expansion and partial peeling of products, and finally damages the products. Therefore, the thermal shock resistance of refractory materials is an important indicator for evaluating their high-temperature performance, and the excellence of thermal shock resistance is also directly related to the service life of refractory materials.
[0003] High chromium castables usually use aluminate cement as a binder and are formed by adding water and vibrating. They are easy to construct and operate, and are widely used due to their high refractoriness, high strength, and strong resistance to slag erosion. However, in high-temperature industries, refractory materials need to have higher thermal shock resistance. Since the binder aluminate cement contains CaO, it is easy to react with the components in the slag to form low-melting products during the use of the castable. CaO corrodes the material and accelerates the damage of the material, thereby greatly reducing the high-temperature performance of the refractory material. Summary of the invention
[0004] The invention provides a cement-free high-chromium castable and a preparation method thereof. The cement-free high-chromium castable is prepared by vibration molding using chromium oxide frit or chromium-aluminum solid solution, chromium oxide fine powder and aluminum oxide micropowder as main raw materials, adding zirconium oxide micropowder, magnesium oxide fine powder and silicon oxide micropowder and the like. The conventional aluminate cement is not used as a binder, thereby reducing the influence of CaO on the slag erosion resistance of the material. The cement-free high-chromium castable has excellent slag erosion resistance and better thermal shock resistance.
[0005] The technical solution adopted by the present invention is as follows: the present invention provides a cement-free high-chromium castable, wherein the original added materials and their weight proportions are: 60-70 parts of chromium oxide frit or chromium-aluminum solid solution particles, 6-20 parts of chromium oxide fine powder, 2-10 parts of aluminum oxide micropowder, 2-5 parts of zirconium oxide micropowder, 0.5-6 parts of magnesium oxide fine powder, 0.5-3 parts of active silicon oxide micropowder, and 0.1-0.15 parts of water reducer.
[0006] Among them, the Cr2O3 content in the chromium oxide frit particles is ≥99wt%; the content of chromium-aluminum solid solution in the chromium-aluminum solid solution particles is ≥95wt%, and the Cr2O3 content in the chromium-aluminum solid solution is ≥85wt%; the particle size grading of the particles is: 5-3mm accounts for 25-40wt%, 3-1mm accounts for 25-45%, and 1-0.1mm accounts for 20-35wt%.
[0007] The Cr2O3 content in the chromium oxide fine powder is ≥99wt% and the particle size is ≤88μm.
[0008] Among them, the Al2O3 content in the alumina fine powder is ≥99wt% and the particle size is ≤5μm.
[0009] The ZrO2 content in the zirconium oxide fine powder is ≥99wt% and the particle size is ≤5μm.
[0010] The MgO content in the magnesium oxide fine powder is ≥97wt% and the particle size is ≤44μm.
[0011] The SiO2 content in the silicon oxide fine powder is ≥94wt% and the particle size is ≤5μm.
[0012] Among them, the water reducer is one of PC-80, PC-A, sodium hexametaphosphate + SM water reducer.
[0013] The preparation method of this cement-free high-chromium castable comprises the following steps: Step 1, weighing and mixing the ingredients according to the original added materials and weight proportions of the cement-free high-chromium castable; Step 2: First, mix the chromium oxide frit or chromium aluminum solid solution particles, add 3-6wt% of water in the total weight of the original feed, stir for 0.5-2 minutes, then add the fine powder, micro powder and water reducing agent in the original feed, and stir evenly; Step 3: pouring and vibrating the evenly stirred mixture to form a cement-free high-chromium casting body.
[0014] The chemical composition of the prepared cement-free high-chromium castable is: Cr2O3 content is 65-90wt%, Al2O3 content is 2-10wt%, MgO content is 0.5-6wt%, ZrO2 content is 2-5wt%, the main crystal phase formed is chromium-aluminum solid solution, and the secondary crystal phase is magnesium-chromium-aluminum composite spinel and baddeleyite.
[0015] The present invention innovatively does not use traditional aluminate cement as a binder to prepare high-chromium castables. The initial strength of the cement-free high-chromium castable is mainly due to the hydration reaction of magnesium oxide to generate brucite and MSH combined cementitious phases, and the main products of the MSH phase are talc and serpentine. After high-temperature sintering, magnesium oxide generated by dehydration of brucite reacts with chromium oxide and aluminum oxide to generate magnesium-chromium-aluminum composite spinel. The thermal expansion coefficients of the spinel and the chromium-aluminum solid solution are different, thereby improving the thermal shock resistance of the cement-free high-chromium castable.
[0016] When the high chromium castable of the present invention uses chromium oxide frit as the raw material, under high temperature use environment, aluminum oxide and chromium oxide are infinitely solid-dissolved in situ to form a chromium-aluminum solid solution, zirconium oxide and magnesium-chromium-aluminum composite spinel are embedded between the chromium-aluminum solid solution, the structure is dense, the strength is high, and the toughness and strength of the material are greatly improved by utilizing its phase change mechanism at high temperature; The present invention uses chromium-aluminum solid solution particles prefabricated at high temperature as the raw material, adds Cr2O3 to the corundum material, and as the temperature rises, Al2O3 and Cr2O3 gradually form a solid solution, the bonding phase is a chromium-aluminum solid solution phase, and chromium-aluminum solid solution particles are prepared at high temperature, the content of chromium-aluminum solid solution in the chromium-aluminum solid solution particles is ≥95wt%, and the content of Cr2O3 in the chromium-aluminum solid solution is ≥85wt%. The chromium-aluminum solid solution still retains the bonding strength under high-temperature use environment, and zirconium oxide and magnesium-chromium-aluminum composite spinel are embedded between the chromium-aluminum solid solution to enhance the high-temperature mechanical properties of the castable.
[0017] The density of the castable matrix can be increased and the porosity can be reduced by adjusting the particle size distribution of the chromium oxide frit or the chromium-aluminum solid solution particles.
[0018] The invention has the beneficial effects of: without using the traditional aluminate cement as a binder, the prepared cement-free high-chromium castable has reduced porosity, improved bulk density, compressive strength and flexural strength. Under high-temperature use environment, magnesium oxide generated after brucite decomposes reacts with chromium oxide and aluminum oxide to generate magnesium-chromium-aluminum composite spinel. Since the thermal expansion coefficients of spinel and chromium-aluminum solid solution are different, the thermal shock resistance of the high-chromium castable can be significantly improved; since the binder does not contain CaO, the influence of CaO on the material's slag erosion resistance is reduced, so the slag erosion resistance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The XRD diagram of the cement-free high-chromium castable of the present invention when kept at 110° C. for 24 hours; Figure 2 This is the XRD diagram of the cement-free high-chromium castable of the present invention when it is kept at 1600° C. for 3 hours; Figure 3 This is a SEM microstructure diagram of the cement-free high-chromium castable of the present invention after being kept at 1600° C. for 3 hours.
[0020] In the figure, AC is chromium-aluminum solid solution, MAC is magnesium-chromium-aluminum spinel, and ZrO2 is baddeleyite. DETAILED DESCRIPTION
[0021] The embodiments of the present invention are described in detail, but they cannot be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art can make several modifications and improvements without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
[0022] The present invention will be further described in detail with reference to the following examples, but the present invention is not limited to these examples. Example 1
[0023] A cement-free high-chromium castable, the original added materials and weight proportions are: 67 parts of chromium oxide frit particles, 13 parts of chromium oxide fine powder, 10 parts of aluminum oxide micropowder, 3 parts of zirconium oxide micropowder, 3 parts of magnesium oxide fine powder, 1 part of active silicon oxide micropowder, and 0.15 parts of PC-80 polycarboxylate water reducer. The particle size distribution of the chromium oxide frit particles is: 5-3mm accounts for 30wt%, 3-1mm accounts for 40%, and 1-0.1mm accounts for 30wt%.
[0024] The preparation method of this cement-free high-chromium castable comprises the following steps: Step 1, weighing and mixing the ingredients according to the original added materials and weight proportions of the cement-free high-chromium castable; Step 2: First, mix the chromium oxide frit particles, add 3.5wt% of water in the total weight of the original feed, stir for 1.5-2 minutes, then add the fine powder, micro powder and water reducing agent in the original feed, and stir evenly; Step 3: pouring and vibrating the evenly stirred mixture to obtain a cement-free high-chromium casting body.
[0025] The test values of the prepared cement-free high-chromium castable are: the apparent porosity is 10.6% after drying at 110°C, and the bulk density is 4.03g / cm 3 , compressive strength 50MPa, flexural strength 10MPa; apparent porosity 19.2% after sintering at 1600℃ for 3h, bulk density 3.92g / cm 3 , compressive strength is 140MPa, flexural strength is 14MPa; thermal shock stability reaches 11 times. Example 2
[0026] A cement-free high-chromium castable, the original added materials and weight proportions are: 65 parts of chromium oxide frit particles, 16 parts of chromium oxide fine powder, 10 parts of aluminum oxide micropowder, 3 parts of zirconium oxide micropowder, 2 parts of magnesium oxide fine powder, 2 parts of active silicon oxide micropowder, and 0.15 parts of sodium hexametaphosphate + SM composite water reducer. The particle size gradation of the chromium oxide frit particles is: 5-3mm accounts for 35wt%, 3-1mm accounts for 45%, and 1-0.1mm accounts for 20wt%.
[0027] The preparation method of this cement-free high-chromium castable comprises the following steps: Step 1, weighing and mixing the ingredients according to the original added materials and weight proportions of the cement-free high-chromium castable; Step 2: First, mix the chromium oxide frit particles, add 3wt% of the total weight of the original feed water, stir for 0.5-1.5 minutes, then add the fine powder, micro powder and water reducing agent in the original feed, and stir evenly; Step 3: pouring and vibrating the evenly stirred mixture to form a cement-free high-chromium casting body.
[0028] The test values of the prepared cement-free high-chromium castable are: the apparent porosity is 11.5% after drying at 110°C, and the bulk density is 4.0g / cm 3 , compressive strength 55MPa, flexural strength 11MPa; apparent porosity 19.5% after sintering at 1600℃ for 3h, bulk density 3.93g / cm 3 , compressive strength is 145MPa, flexural strength is 14.5MPa; thermal shock stability reaches 12 times. Example 3
[0029] A cement-free high-chromium castable, the original added materials and weight proportions are: 70 parts of chromium oxide frit particles, 13 parts of chromium oxide fine powder, 8 parts of aluminum oxide micropowder, 2 parts of zirconium oxide micropowder, 3 parts of magnesium oxide fine powder, 2 parts of active silicon oxide micropowder, and 0.1 part of PC-A type polycarboxylate water reducer. The particle size gradation of the chromium oxide frit particles is: 5-3mm accounts for 40wt%, 3-1mm accounts for 35%, and 1-0.1mm accounts for 25wt%.
[0030] The preparation method of this cement-free high-chromium castable comprises the following steps: Step 1, weighing and mixing the ingredients according to the original added materials and weight proportions of the cement-free high-chromium castable; Step 2: First, mix the chromium oxide frit particles, add 4.5wt% of water in the total weight of the original feed, stir for 1-2 minutes, then add the fine powder, micro powder and water reducing agent in the original feed, and stir evenly; Step 3: pouring and vibrating the evenly stirred mixture to form a cement-free high-chromium casting body.
[0031] The test values of the prepared cement-free high-chromium castable are: the apparent porosity is 12.3% after drying at 110°C, and the bulk density is 4.0g / cm 3 , compressive strength 56MPa, flexural strength 11MPa; apparent porosity 19.6% after sintering at 1600℃ for 3h, bulk density 3.93g / cm 3 , compressive strength is 135MPa, flexural strength is 13.5MPa; thermal shock stability reaches 10 times. Example 4
[0032] A cement-free high-chromium castable, the original added materials and weight proportions are: 67 parts of chromium-aluminum solid solution particles, 15 parts of chromium oxide fine powder, 10 parts of aluminum oxide micropowder, 3 parts of zirconium oxide micropowder, 1 part of magnesium oxide fine powder, 2 parts of active silicon oxide micropowder, and 0.15 parts of PC-A type polycarboxylate water reducer. The particle size distribution of the chromium-aluminum solid solution particles is: 5-3mm accounts for 25wt%, 3-1mm accounts for 40%, and 1-0.1mm accounts for 35wt%.
[0033] The preparation method of this cement-free high-chromium castable comprises the following steps: Step 1, weighing and mixing the ingredients according to the original added materials and weight proportions of the cement-free high-chromium castable; Step 2: First, mix the chromium oxide frit particles, add 6wt% of water in the total weight of the original feed, stir for 1.5-2 minutes, then add the fine powder, micro powder and water reducing agent in the original feed, and stir evenly; Step 3: pouring and vibrating the evenly stirred mixture to form a cement-free high-chromium casting body.
[0034] The test values of the prepared cement-free high-chromium castable are: the apparent porosity is 12.5% after drying at 110°C, and the bulk density is 4.05g / cm 3 , compressive strength 60MPa, flexural strength 12MPa; apparent porosity 19.8% after sintering at 1600℃ for 3h, bulk density 3.95g / cm 3 , compressive strength is 150MPa, flexural strength is 15MPa; thermal shock stability reaches 12 times.
[0035] The composition of the binder phase of the cement-free high-chromium castable is affected by the magnesium / silicon ratio. When the ratio is large, the brucite phase is more (see Figure 1 ), magnesia is generated after dehydration of brucite at high temperature, and reacts with chromium oxide and aluminum oxide in the castable to form magnesium-chromium-aluminum composite spinel (see Figure 2 , Figure 3), due to the different thermal expansion coefficients of spinel and chromium aluminum solid solution in the castable, the thermal shock resistance of the material is improved. The high chromium castable of the present invention does not use traditional aluminate cement as a binder, so it contains almost no CaO. During the use of the castable, the influence of CaO on the material's anti-slag erosion performance will be correspondingly reduced.
Claims
1. A cement-free high-chromium castable, characterized in that: The original added materials and their weight proportions are: 60-70 parts of chromium oxide frit or chromium aluminum solid solution particles, 6-20 parts of chromium oxide fine powder, 2-10 parts of aluminum oxide micropowder, 2-5 parts of zirconium oxide micropowder, 0.5-6 parts of magnesium oxide fine powder, 0.5-3 parts of active silicon oxide micropowder, and 0.1-0.15 parts of water reducer.
2. The cement-free high-chromium castable according to claim 1, characterized in that: The Cr2O3 content in the chromium oxide frit particles is ≥99wt%, the chromium aluminum solid solution content in the chromium aluminum solid solution particles is ≥95wt%, and the Cr2O3 content is ≥85wt%; the particle size gradation of the particles is: 5-3mm accounts for 25-40wt%, 3-1mm accounts for 25-45wt%, and 1-0.1mm accounts for 20-35wt%.
3. The cement-free high-chromium castable according to claim 1, characterized in that: The Cr2O3 content in the chromium oxide fine powder is ≥99wt% and the particle size is ≤88μm.
4. The cement-free high-chromium castable according to claim 1, characterized in that: The Al2O3 content in the alumina fine powder is ≥99wt% and the particle size is ≤5um.
5. The cement-free high-chromium castable according to claim 1, characterized in that: The ZrO2 content in the zirconium oxide fine powder is ≥99wt% and the particle size is ≤5 um.
6. The cement-free high-chromium castable according to claim 1, characterized in that: The MgO content in the magnesium oxide fine powder is ≥97wt% and the particle size is ≤44 um.
7. The cement-free high-chromium castable according to claim 1, characterized in that: The SiO2 content in the silicon oxide fine powder is ≥94wt% and the particle size is ≤5um.
8. The cement-free high-chromium castable according to claim 1, characterized in that: The water reducer is one of PC-80, PC-A, sodium hexametaphosphate + SM water reducer.
9. The cement-free high-chromium castable according to claim 1, characterized in that: The chemical composition of the prepared cement-free high-chromium castable is: Cr2O3 content is 65-90wt%, Al2O3 content is 2-10wt%, MgO content is 0.5-6wt%, ZrO2 content is 2-5wt%, the main crystal phase formed is chromium-aluminum solid solution, and the secondary crystal phase is magnesium-chromium-aluminum composite spinel and baddeleyite.
10. The method for preparing a cement-free high-chromium castable according to claim 1, characterized in that: The following steps are involved: Step 1, weighing and mixing the ingredients according to the original added materials and weight proportions of the cement-free high-chromium castable; Step 2: First, mix the chromium oxide frit or chromium aluminum solid solution particles, add 3-6wt% of water in the total weight of the original feed, stir for 0.5-2 minutes, then add the fine powder, micro powder and water reducing agent in the original feed, and stir evenly; Step 3: pouring and vibrating the evenly stirred mixture to obtain a cement-free high-chromium casting body.
Citation Information
Patent Citations
Application method of cement-free castable
CN103553645A
Cement-free aluminum-magnesium-chromium castable taking aluminum-chromium slag as main raw material as well as preparation method and application of cement-free aluminum-magnesium-chromium castable
CN112679201A
In-situ spinel-containing refractory castable combined with magnesium oxide, and preparation method of refractory castable
CN113173780A
Magnesium-aluminum-chromium spinel castable and preparation method thereof
CN115385681A
Chromia-enriched castable refractory substance, and precast block using the same
JP2010280540A
Cited By
High-resistance and strong-thermal-shock ceramic material for nuclear waste treatment and preparation method of high-resistance and strong-thermal-shock ceramic material
CN121494588A